Measurements of Greenhouse Gas Flux from Composting Green-Waste Using Micrometeorological Mass Balance and Flow-Through Chambers. Issue 2 (3rd April 2019) - Kent, Eric R.; Bailey, Shannon K.; Stephens, Jilmarie; Horwath, William R.; Paw U, Kyaw Tha
Abstract: Greenhouse gases (GHGs) are produced during the composting process, but few studies have measured emissions from a full-scale windrow of composting green-waste. This is important for evaluating composting as a waste management option and for understanding how changes to current composting management practices could help reduce emissions. This study uses micrometeorological mass balance (MMB) and open flow-through chamber techniques to measure emissions of carbon dioxide (CO2 ), methane (CH4 ), and nitrous oxide (N2 O) from a windrow of composting green-waste in Northern California. The MMB technique yielded mean upwind–downwind concentration differences over the study period that showed sourcing of all three GHGs. CO2 showed a stronger signal than CH4 and N2 O. A strong diel pattern was found in the concentration differences at lower levels and fluxes of CO2, with substantial noise likely obscuring any possible daily patterns for CH4 and N2 O. Fluxes normalized by the time since the previous turn event revealed an initial rapid rise in CO2 concentration differences (at lower levels) and fluxes, peaking close to 13 h after the turn event followed by a gradual decline. The same pattern was not as clear for the other two gases but overall declines in concentration differences and fluxes were apparent with increasing time since the previous turn event. Substantial differences between MMB and chamber calculated fluxes were found, due to both differences in the techniques as well as sampling frequency.